Hesperidin Interaction with HMG-CoA-Reductase Enzyme in Hypercholesterolemia: A Study in Silico - Annisa Rizqi Dwi Oktaviani; Veronica Shania Aprillia; Eko Suhartono; Noer Komari (Fakultas Kedokteran Universitas Lambung Mangkurat, 2021)
Abstract: Dyslipidemia is a degenerative disease occurred with increased levels of fat and cholesterol levels in blood. One of the proteins used as anti-cholesterol is an HMG-CoA-Reductase. Hesperidin in orange peel can reduce cholesterol levels by interacting with HMG-CoA-Reductase. To prove this, an in silico method was used by using swissdock.ch (http://swissdock.ch/docking#). The receptor protein in dyslipidemia was obtained from the RCSB Protein Data Bank (https://www.rcsb.org) namely HMG-CoA-reductase receptor with code PDB: 1HW9. The natural ligand, hesperidin, was obtained from PubChem with code: 10621 (https://pubchem.ncbi.nlm.nih.gov/). Protein was prepared by omitting the natural ligand residues present in the protein. Ligand and protein preparations were used by the chimera 1.15. The result of this study indicated that the interaction of hesperidin with several amino acid recidues was predicted to provide inhibitory activity on HMG-CoA reductase as the protein target. Inhibition of HMG-CoA reductase will reduce mevalonate synthesis so that cholesterol levels will decrease. Keywords: hesperidin, HMG-CoA-Reductase, cholesterol, dyslhahipidemia